Cluster randomized controlled trial of volitional and motivational interventions to improve bowel cancer screening uptake: A population-level study. (November 2020) - Wilding, Sarah; Tsipa, Anastasia; Branley-Bell, Dawn; Greenwood, Darren C.; Vargas-Palacios, Armando; Yaziji, Nahel; Addison, Caroline; Kelly, Phil; Day, Fiona; Horsfall, Kate; Conner, Mark; O'Connor, Daryl B.
Abstract: Objectives. Colorectal cancer (CRC) is a leading cause of cancer death worldwide, although effective uptake of bowel cancer screening is below 60% in England. This trial investigated the influence of volitional and motivational interventions and their combination on increasing guaiac fecal occult blood testing (gFOBT) screening uptake. Method. In total, 34, 633 participants were recruited (via North-East of England bowel cancer screening hub) into a 2×2 factorial cluster randomized controlled trial. Social norm-based motivational intervention (SNA); Implementation intention-based Volitional Help Sheet (VHS); Combined intervention (SNA+VHS); Treatment as usual control. Screening rate (gFOBT kit return rate within 8 weeks of invitation) was the primary outcome. Results. Screening kits were returned by 60% of participants ( N =20, 847/34, 633). A substantial imbalance was observed in participant characteristics, participants in the combined intervention group were younger and more likely to be first time invitees. Adjusted analyses found insufficient evidence that any of the interventions were different to control (Combined: OR = 1.18, 95% CI 0.97-1.44; SNA alone: OR =0.93; 95% CI : 0.76-1.15; VHS alone OR = 0.88; 95% CI : 0.75-1.03). Subgroup analyses demonstrated a significant beneficial effect of the combined intervention in the youngest age group compared to control ( OR = 1.27; 95% CI: 1.05-1.54). Conclusions. The study did not support any benefit of either VHS or SNA interventions alone on bowel cancer screening uptake. The combined SNA+VHS intervention was significantly different from control only in the youngest age group in adjusted analyses. However, the magnitude of effect in the youngest age group suggests that further testing of VHS plus SNA interventions in carefully targeted populations may be warranted. Highlights: Two brief behaviour change interventions were tested on bowel screening uptake. Screening kits were returned by 60% of participants in the study. A social norm-based motivational intervention had no effect on uptake. An implementation intention-based volitional intervention had no effect on uptake. The combined effect of both interventions did not increase uptake.